Засоби образної репрезентації знань про риму в поетичному тексті - Мовчун, Лариса; Movchun, Larysa (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття присвячена проблемі лінгвістичного дослідження української рими, зокрема питанню співвідношення теорії римології і поетичної практики. З’ясовано способи репрезентації римологічних знань образними засобами, основними з яких є епітет і метафора. The article is dedicated to the problem of linguistic research of the Ukrainian rhyme, particularly to the issue of rhymology theory and poetic practice correlation. The purpose was to illuminate the ways an author reproduces his knowledge about the rhyme in the poetic text by the figurative means. Theoretical thesis consists of five parts: 1) rhymed and unrhymed poetry; 2) rhyme definition; its structure; 3) rhyme varieties; 4) functions of rhyme; 5) knowledge gained by means of practical experience. The last concerns the rhyme’s place in the scenario of creative process. In the poetic text the word rhyme has several meanings: common language, terminological and figurative. It becomes the basis of image creation. The poets often use the rhymology terms vers libre, clausula, assonance, exact / banal / poor / verbal-inflection rhyme etc. Metaphors, epithets, comparisons and expressive synonyms of terms are the means of figurative representation of rhymology knowledge as well.
Means of Figurative Representation of Knowledge about the Rhyme in the Poetic Text
Keywords: рима; римологія; поетичний текст; епітет; метафора; rhyme; rhymology; poetical text; epithet; metaphor